Identification of cervicovaginal flora in liquid based Surepath™: Results of rodeo study - Stein, Maíra Degiovani; Fregnani, José Humberto T. G.; Scapulatempo, Cristovam; Filho, Adhemar Longatto (Citotech Online - Case Review, 2015)
Aim of the study: To evaluate the morphological pattern of cervicovaginal flora elements in liquid based SurePath™ cytology. Material and methods: During the period between May, 2010 and August, 2011, 10.166 gynecological samples preserved in liquid based SurePath were evaluated at Barretos Cancer Hospital, in order to identify cervicovaginal flora. Results: Data showed that Lactobacillus sp were observed in 48.92% of the exams, Bacilli in 25.19%, Cocci in 11.77%, Candida sp in 5.14%, Gardnerella sp in 11.41%, Trichomonas vaginalis in 0.57% and in 0.02% of the exams the effects of Herpes virus. Any microorganism was observed in 2.45% of the exams. Conclusion: This study demonstrates that the liquid based preparation does not interfere with the identification of cervicovaginal flora.